Proposta de produto informativo sobre o manejo de resíduos sólidos de saúde no Hospital de Clínicas de Uberlândia - Vitorino, Sílvia Maria Aparecida (2015)
The waste of health services (WHS) is a central question, awakens the interest due to damage that may to the cause public health and the environment. This report presents the diagnosis of the management of WHS by analysis and efficiency of the Plan about Management of Waste of Health Services - (MPHSW) of the Hospital das Clínicas of the Federal University of Uberlandia - (HCU), shows the result of the investigation about he resours that have generated potential problems with the management of the WHS, and shows the proposals of implementing the product in the institution, as well as bring data about the product. In Brazil, between the years 2009 to 2013, the available databases record, the production of 183.5 thousand (t) /day of WHS (ANVISA 2010). In Uberlandia, 1.69T/day of RSS is produced in the HCU. The paper has as the main gool guidelines expected in the plan, in order to provide guidance on the proper disposal of each residue. The research has purpose applied, objective exploratory and descriptive, documental procedure of nature qualitative quantitative, and on-site observation. Therefore, the study of the management of WHS, is relevant, because promote the knowledge of the variables that has provoked the not effectiveness of this management tool, allowing to establish prevention measures and control of the events that predispose those occurrences.